UMP volunteers draw up mission to assist Kota Palu victims - Nor Fatin Nabilah, Mohd Tahir (2019)
Stirred by the plight of victims suffering from the double natural disasters of earthquake and tsunami, which hit Kota Palu, Sulawesi, Indonesia, last September 28, Universiti Malaysia Pahang (UMP) volunteers -comprising Students Movement (GPS) in collaboration with the Chemical Engineering Students Association (CHEST) – have drawn up a programmed called Palu Humanitarian Mission to help lighten the former’s burden.